Cr doping effect in B-site of La0.75Sr0.25MnO 3 on its phase stability and performance as an SOFC anode - Zheng, Y.; Ran, R.; Shao, Zongping (2009)
La0.75Sr0.25Cr y Mn1-y O 3 (LSCM) (y = 0.0-0.6) composite oxides were synthesized by a complexing process of combining ethylene diamine tetraacetic acid (EDTA) and citrate. X-ray diffraction (XRD), temperature-programmed reduction, electrical conductivity, I-V polarization, and impedance spectroscopy were conducted to investigate the Cr doping effect of La0.75Sr0.25MnO 3 on its phase stability and electrochemical performance as a solid-oxide fuel cell (SOFC) anode. The chemical and structural stabilities of the oxides increased steadily with increasing Cr doping concentration, while the electrical conductivity decreased on the contrary. At y = 0.4, the basic perovskite structure under the anode operating condition was sustained. a cell with 0.5-mm-thick scandia-stabilized zirconia electrolyte and La 0.75Sr0.25Cr y Mn1-y O3 anode delivered a power density of ~15 mW•cm-2 at 850°C. © 2009 Journal Publishing Center of University of Science and Technology Beijing and Springer-Verlag GmbH.